The Warden level 5 - Trollope A. Anthony (Penguin Readers)
The tranquil atmosphere of the cathedral town of Barchester is shattered when a scandal breaks concerning the financial affairs of a Church-run almshouse for elderly men. In the ensuing furore, Septimus Harding, the almshouse`s well-meaning warden, finds himself pitted against his daughter`s suitor Dr John Bold, a zealous local reformer.